2020
DOI: 10.1111/infi.12383
|View full text |Cite
|
Sign up to set email alerts
|

Dirty money: Does the risk of infectious disease lower demand for cash?

Abstract: The COVID‐19 pandemic is a global crisis like no other in modern times, and there is a growing apprehension about handling potentially contaminated cash. This paper is the first empirical attempt in the literature to investigate whether the risk of infectious diseases affects demand for physical cash. Since the intensity of cash use may influence the spread of infectious diseases, this paper utilizes two‐stage least squares methodology with instrumental variable to address omitted variable bias and account for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…The dependent variable is the nominal cash in circulation as a share of nominal GDP, which is frequently used in the literature (Armelius et al 2021;Cevik 2020). Using the share of nominal cash in circulation in nominal GDP is beneficial for three reasons.…”
Section: Data Sources and Research Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…The dependent variable is the nominal cash in circulation as a share of nominal GDP, which is frequently used in the literature (Armelius et al 2021;Cevik 2020). Using the share of nominal cash in circulation in nominal GDP is beneficial for three reasons.…”
Section: Data Sources and Research Methodologymentioning
confidence: 99%
“…In some studies, the importance of the shadow economy for cash demand is not confirmed (Jobst and Stix 2017a;Takala and Viren 2010) or the results are mixed (Deutsche Bundesbank 2019; Seitz et al 2018). The role of the shadow economy has been confirmed in various studies Goodhart 2020a, 2020b;Cevik 2020;Reimers et al 2020). In all these studies, the Multiple Indicator-Multiple Cause (MIMIC) model was adopted, and the authors adopted the share of the self-employed in total employment, VAT rates, and cigarette consumption as variables allowing estimates of the shadow economy.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter include , , Coyle et al (2021), Chen et al (2020), Auer et al (2020), Wisniewski et al (2021). Cevik (2020) shows that the risk of infection reduced the demand for cash. Using highfrequency transaction data, Ardizzi et al (2020) find that cash use declined and card use increased in Italy during COVID.…”
Section: Literature Reviewmentioning
confidence: 99%